Vulnerability of Southeast Greenland Glaciers to Warm Atlantic Water From Operation IceBridge and Ocean Melting Greenland Data. Issue 6 (25th March 2018) - Millan, R.; Rignot, E.; Mouginot, J.; Wood, M.; Bjørk, A. A.; Morlighem, M.
Abstract: We employ National Aeronautics and Space Administration (NASA)'s Operation IceBridge high‐resolution airborne gravity from 2016, NASA's Ocean Melting Greenland bathymetry from 2015, ice thickness from Operation IceBridge from 2010 to 2015, and BedMachine v3 to analyze 20 major southeast Greenland glaciers. The results reveal glacial fjords several hundreds of meters deeper than previously thought; the full extent of the marine‐based portions of the glaciers; deep troughs enabling warm, salty Atlantic Water (AW) to reach the glacier fronts and melt them from below; and few shallow sills that limit the access of AW. The new oceanographic and topographic data help to fully resolve the complex pattern of historical ice front positions from the 1930s to 2017: glaciers exposed to AW and resting on retrograde beds have retreated rapidly, while glaciers perched on shallow sills or standing in colder waters or with major sills in the fjords have remained stable. Plain Language Summary: Over the last century, the glaciers in southeast Greenland have exhibited different behaviors from one fjord to the next. This complex spatial pattern has been difficult to explain due to a dearth of information about fjord depths and ocean properties in the fjords. Here we use National Aeronautics and Space Administration's Operation Icebridge and Ocean Melting Greenland data to map the depth of fjords and glacier bed topography. We detect glacial valleys several hundreds of meters deeper than previously thought. We find that retreating glaciers stood in deep valleys exposed to warm Atlantic water, whereas stable glaciers are perched on sills away from warm water. These results improve our understanding of the evolution of the glaciers and their impact on mass balance of the ice sheet. Key Points: A multisensor approach combining radar sounding, multibeam, and gravity is used to solve the problem of bed mapping in southeast Greenland The approach is evaluated using sparse radar data, uncertainty of the gravity inversion, and ice front fluxes versus balance fluxes We are able to interpret the pattern of past and recent retreat of a large fraction of the glaciers, which was not possible before